Different phases of a system of hard rods on three dimensional cubic lattice. (28th November 2017) - Vigneshwar, N; Dhar, Deepak; Rajesh, R
Abstract: We study the different phases of a system of monodispersed hard rods of length k on a cubic lattice, using an efficient cluster algorithm able to simulate densities close to the fully-packed limit. For k ⩽ 4, the system is disordered at all densities. For k = 5, 6, we find a single density-driven transition, from a disordered phase to high density layered-disordered phase, in which the density of rods of one orientation is strongly suppressed, breaking the system into weakly coupled layers. Within a layer, the system is disordered. For k ⩾ 7, three density-driven transitions are observed numerically: isotropic to nematic to layered-nematic to layered-disordered. In the layered-nematic phase, the system breaks up into layers, with nematic order in each layer, but very weak correlation between the ordering directions of different layers. We argue that the layered-nematic phase is a finite-size effect, and in the thermodynamic limit, the nematic phase will have higher entropy per site. We expect the systems of rods in four and higher dimensions will have a qualitatively similar phase diagram.